Seis escenarios de la historia - Palacios Bañuelos, Luis, 1944- (Madrid : Universidad Rey Juan Carlos, Servicio de Publicaciones : Dykinson, S.L., 2010)
A selection of the author's works from the last ten years (as of 2007).
Online resource; title from PDF title page (Digitalia, viewed December 1, 2016)
Keywords: Spaniards -- Biography; Spain -- History -- 19th century; Spain -- History -- 20th century; Spain -- Economic conditions; Electronic books